ANALISIS EFEKTIFITAS IKLAN MEDIA TELEVISI INDOMIE MIE GORENG â€œBULGOGIâ€ MENGGUNAKAN EPIC MODEL DI KOTA PONTIANAK - B11109076, Evi Triana (Jurnal Manajemen Update, 2015)
In the face of increasingly fierce competition, companies must implement appropriate marketing strategies in marketing their products. One marketing strategy is to provide information about the products that are marketed to consumers through advertisement in varios media. Advertising gets spotlight since aspects of information is important in the business, effective avertising activities deemed able to influence the propensity to comsume in the community. Purpose of this study was to determine the effectiveness of advertising through television media, as measured by the method of EPIC. Effective advertising will change public knowledge about the availability and characteristics of some products, the elasticity of demand for the product will be greatly influenced by advertising activity. This study uses a simple tabulation analysis and the average score. Population used is Pontianak city communities with the criteria of respondents had seen the the ad. While the sample is used as many as 100 people with purposive sampling method. From the average score of respondentsâ€™ opinions on the statements that measure the dimension of the result of 3,904 empathy, persuation dimensions of 3,57, 3,64 dimensional impact, and of the communication dimension of 3,672. EPICrate value of 3,7, this value indicates that the overall entry in the effective scale range. It can be concluded that the ad fried noodle products BULGOGI considered effective. Key word : EPIC is Model, Advertising Effectiviness.